Synthetic neuroactive steroids as new sedatives and anaesthetics: Back to the future. (10th January 2022) - Manzella, Francesca M.; Covey, Douglas F.; Jevtovic‐Todorovic, Vesna; Todorovic, Slobodan M.
Abstract: Since the 1990s, there has been waning interest in researching general anaesthetics (anaesthetics). Although currently used anaesthetics are mostly safe and effective, they are not without fault. In paediatric populations and neonatal animal models, they are associated with learning impairments and neurotoxicity. In an effort to research safer anaesthetics, we have gone back to re‐examine neuroactive steroids as anaesthetics. Neuroactive steroids are steroids that have direct, local effects in the central nervous system. Since the discovery of their anaesthetic effects, neuroactive steroids have been consistently used in human or veterinary clinics as preferred anaesthetic agents. Although briefly abandoned for clinical use due to unwanted vehicle side effects, there has since been renewed interest in their therapeutic value. Neuroactive steroids are safe sedative/hypnotic and anaesthetic agents across various animal species. Importantly, unlike traditional anaesthetics, they do not cause extensive neurotoxicity in the developing rodent brain. Similar to traditional anaesthetics, neuroactive steroids are modulators of synaptic and extrasynaptic γ‐aminobutyric acid type A (GABAA ) receptors and their interactions at the GABAA receptor are stereo‐ and enantioselective. Recent work has also shown that these agents act on other ion channels, such as high‐ and low‐voltage‐activated calcium channels. Through these mechanisms of action, neuroactive steroids modulate neuronal excitability, which results in characteristic burst suppression of the electroencephalogram, and a surgical plane of anaesthesia. However, in addition to their interactions with voltage and ligand gated ions channels, neuroactive steroids interact with membrane bound metabotropic receptors and xenobiotic receptors to facilitate signaling of prosurvival, antiapoptotic pathways. These pathways play a role in their neuroprotective effects in neuronal injury and may also prevent extensive apoptosis in the developing brain during anaesthesia. The current review explores the history of neuroactive steroids as anaesthetics in humans and animal models, their diverse mechanisms of action, and their neuroprotective properties. Abstract : For some time, it has been known that neuroactive steroids can produce sedation and anesthesia. This review follows the history of steroid anesthetics, their mechanisms of action, and their unique neuroprotective properties which make them ideal targets for future therapeutics.